Making the best of a bad sample: Comparison of DNA extraction and quantification methods using sub-optimally stored Ixodes ricinus ticks - Andrea P. Cotes-Perdomo; Kenedith Méndez-Gutierrez; Kristian Alfsnes; Åshild K. Andreassen; Andrew Jenkins (PLoS ONE, 2025)
The primary aim of this study was to evaluate the performance of four DNA extraction methods on a collection of 200 sub-optimally stored Ixodes ricinus ticks from Southeastern Norway (177 nymphs, 11 males and 12 females). The methods were ammoniium hydroxide hydrolysis of homogenised or intact ticks and two commercial silica membrane-based kits, the QIAGEN Blood and Tissue kit and the QIAGEN Mini kit. DNA was evaluated by spectrophotometry, fluorometry, agarose gel electrophoresis and quantitative PCR. The second aim was to compare methods of evaluating the yield and purity. All four extraction methods provided amplifiable DNA, but the yield was variable (median 151 ng, range 0.13 to 4500 ng). DNA yields were not significantly different across the methods. Nine of 200 samples were inhibitory, all of which were ammonium hydroxide extracts of homogenised ticks. DNA purity, as judged by A260/280 ratios, was low; it was highest (mean = 1.63) for the Qiagen Blood and Tissue kit with the other methods showing values averaging 1.44. DNA yield measurements using qPCR, fluorometry (Qubit), drop spectrophotometry (NanoDrop) and gel electrophoresis (E-gels) correlated poorly, r ranging from <0 to 0.9 with no systematic pattern (average 0.4), probably reflecting the effects of low purity, low concentrations and differing amounts of single- and double-stranded DNA. Neoehrlichia mikurensis and Borrelia burgdorferi s.l. were detected in 5 and 13% of samples, respectively by qPCR. Our findings indicate that for the purposes of qPCR analysis, ammoniium hydroxide hydrolysis of intact ticks, a very cheap and simple method is as good as any of the other methods tested.